Rheology, Strength and Durability Characteristics of Alccofine Blended Fibre Reinforced Self Consolidating Concrete - Baby, Bletty; Anto, Jerry; Johny, Basil; S, Sreenath (International Journal of Engineering and Technology, 2018)
In this study, observations were made on the effect of blending cement with fly ash and Alccofine on the fresh and hardened properties of micro steel fibre reinforced self-consolidating concrete (SCC). SCC mixes were prepared based on EFNARC guidelines. Blending has been done by replacing 5%, 10% and 15% of cement with Alccofine. Slump flow, L-box and V-funnel tests were conducted to study the flow characteristics of SCC. Compressive strength, split tensile strength, and flexural strength tests were performed to assess the strength characteristics. It was observed that the SCC with 10% replacement of cement with Alccofine showed better results than the other mixes. Further, the modification of the optimum blend with 10% Alccofine was made by adding variable percentages (0.5%, 1% and 1.5% by volume) of micro steel fibres and strength tests were conducted to optimise the fibre content. The strength degradation of the SCC with optimum Alccofine and fibre content exposed to alkaline, chloride and sulphate solutions was also studied.